The Concept of Sakinah from a Psychological Perspective in Tafsir Al-Misbah - Putri Trianda; Abrar Dawud (International Journal of Multidisciplinary Research of Higher Education, 2026)
The concept of sakinah in the Qur’an represents an important value associated with inner tranquility, emotional stability, and closeness to Allah. This study aims to analyze the concept of sakinah in M. Quraish Shihab’s Tafsir Al-Misbah and examine its relevance to cognitive psychology. This study employed a qualitative descriptive approach with a library research design. The primary data source was Tafsir Al-Misbah, particularly its interpretation of verses concerning sakinah in Surah Al-Baqarah [2]: 248, Surah At-Tawbah [9]: 26 and 40, Surah Al-Fath [48]: 4, 18, and 26, and Surah Ar-Rum [30]: 21. Secondary data were obtained from books, journal articles, and other scholarly literature related to Qur’anic exegesis, sakinah, and cognitive psychology. The data were analyzed using content analysis. The findings reveal that sakinah in Tafsir Al-Misbah refers not only to outward calmness but also to inner tranquility arising from faith, self-control, positive thinking, and the ability to regulate emotions. These findings demonstrate the relevance of sakinah to cognitive psychology, particularly in promoting psychological tranquility among modern individuals through the integration of spiritual values and healthy thought processes.